Controle microbiano da cigarrinha-do-milho Dalbulus maidis (DeLong & Wolcott) (Hemiptera: Cicadellidae) com os fungos entomopatogênicos Cordyceps fumosorosea e Beauveria bassiana seus efeitos sobre o complexo de enfezamentos da cultura do milho e impacto sobre a produtividade - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2023)
The corn leafhopper Dalbulus maidis (DeLong & Wolcott) (Hemiptera: Cicadellidae) has become a challenge for the management of pests in the corn crop as a vector of stunting. In this context, it is essential to understand the dynamics of disease occurrence and its relationship with the damage caused to the corn crop, in order to guide the management of the insect vector. This research aims to understand how microbiological control with the fungi Cordyceps fumosorosea and Beauveria bassiana can be used in the management of the corn leafhopper and its effects in reducing the stunting complex in the corn crop. For this, experiments were carried out in order to evaluate the effectiveness of biological insecticides (Octane, FlyControl, Ecobass, Ballveria and Bometil) in isolated spraying, intercalated or associated with acephate in reducing the population of corn leafhopper, attesting to the pathogenicity of the fungi present in biological insecticides and their effects on the incidence of stunting. In addition, the population density of D. maidis was monitored during the crops of grain and intercrop period through yellow traps installed around the area where the test was conducted and the collected insects were submitted to a PCR test in the laboratory to verify the presence of stunting. Foliar sprays had low efficacy in controlling adults of D. maidis. The incidence of stunting was higher when the plants coexisted with a high population density of the pest in the early stages of development. Laboratory analyzes indicated the prevalence of phytoplasma in relation to spiroplasma in corn plants, on the other hand, the leafhoppers analyzed did not show prevalence of spiroplasma or phytoplasma. The average number of leafhoppers infected with fungi after spraying B. bassiana was 25,7%, the association of B. bassiana and Metarhizium anisopliae caused infection on 74% of the collected leafhoppers, while C. fumosorosea resulted in 35% of infections. The treatments that resulted highest yields in the 2021/2022 crop year were Octane intercalated with acephate with 743 kg ha-1 , followed by acephate with 558 kg ha-1 and Ecobass intercalated with acephate with 477,2 kg ha-1. On average, the isolated biological treatments resulted an economic result of 300 kg ha-1 , while the intercalated use of biological and chemical treatments resulted in 516 kg ha-1. While in the 2022/2023 crop year, Ballveria (100) and FlyControl (500) treatments had the highest productivity balances with 666,8 and 616,6 kg ha-1. In the spraying associated with biological and chemical insecticides, the acephate (1000) + Ballveria (100) treatment showed a balance of 768,3 kg ha-1, being 104,5 kg ha-1 higher than the acephate (1000) + Octane treatment (500) and 187,1 kg ha-1 higher than treatment with acephate (1000) + FlyControl (100). In conclusion C. fumosorosea and B. bassiana are promising agents for the control of D. maidis and provide bases for the use of biological insecticides in the management of corn leafhopper applied in isolation or in association with chemical insecticides.
Keywords: Dalbulus maidis; enfezamentos; controle microbiano; milho; Dalbulus maidis; stunting; microbiological control; corn; CNPQ::CIENCIAS AGRARIAS::AGRONOMIA